Madhusadda Rvhe toṅʻ Kyoʻ cvā bhvaiʹ ra rupʻ seʺ maṅʻʺ sa mīʺ krīʺ Ūʺ Phūʺ Ññui e* bhava jātʻ kroṅʻʺ - Sakʻ Chve, Cha rā (Cā pe Bimānʻ thutʻ praññʻ sūʹ lakʻ cvai cā cañʻ, 1993)
Biography of the Burmese puppetteer, stage performer, and female impersonator Ūʺ Ph̄ʺ Ññui, 1862-1929.